PATIENT IDENTIFICATION PRACTICES IN A PEDIATRIC INTENSIVE CARE UNIT - Suelen Cristina Zandonadi Bernal; Daiane Cortez Raimondi; João Lucas Campos de Oliveira; Kelly Cristina Inoe; Laura Misue Matsuda (Universidade Federal do Paraná, 2018)
Objective: to investigate patient identification practices in a pediatric intensive care unit. Method: a cross-sectional study was carried out in three public hospitals in the South of Brazil.Data collection (identifying items) was performed in 2015, through non-participant observation and consultation of the medical records.The data were analyzed using descriptive statistics.Results: of the 96 patients observed, 94 (98%) had an identification nameplate next to the bed.No identification wristbands were used.The identification nameplates included the child's name (95%), age (31%) and the name of the person responsible (78%).Of those identified by name (n=89), 62 (70%) were complete.In the medical prescription and nursing record there were deficiencies in the registration of the full name, date of birth and names of the parents.Conclusion:despite the wide range of resources, there was a deficiency in the systematization of patient identification, affecting (un)safe care.